The impact of mass media uses and gratifications on voters: case of Egypt 2012 presidential elections - Phillips, Nouran Victor (AUC Knowledge Fountain, 2012)
This paper clarifies the role of mass media through the Uses and Gratifications approach during the Egyptian 2012 Presidential Elections campaigns. The main focus of this study aims at studying the role of mass media in shaping Egyptian votersâ final decision. In addition, how voters used mass media to search for information to follow up the presidential candidatesâ campaigns by exploring the factors that predisposed voters to make their voting decisions. In light of Elihu Katz (1959) question â What do people do with media?â and Blumler and McQuail (1969) concern about how people used the media to gather information about General Elections in Britain in 1965, they developed the Uses and the Gratifications Theory in order to study the relationship between voters and the media. In addition, in the 21st century, the Uses and Gratification Theory had been recognized as a tool to understand audience behaviors and usage patterns and perceptions from the media. Thus, the theory is used to teach communicators how to communicate better with their target audience. Data was collected through self-administered surveys in both languages, English and Arabic. The sample examined is a â Purposive Sampleâ including only Egyptian voters who participated in the presidential elections in 2012 whether in round one or round two or both. The sample was chosen according to the votersâ eligibility of age authorized to voting criteria, geographical residence was limited to Egyptâ s â Greater Cairo Cityâ and interest in media political participation reflected in making actual voting procedure in 2012 Egyptian Presidential Elections. The findings of the study concluded that respondents voted during the 2012 Egyptian Presidential Elections had a great hope in a better future for the country. Respondents who are affiliated to political parties or movements had a greater tendency to be satisfied by political campaigns on different mass media channels. However, Respondents who were party member did not build their perceptions about the candidates from the media.